Yield losses due to powdery mildew disease in fenugreek (Trigonella foenum-graecum L.) - Jhorar, A S Rathi, P P Gupta, B S (Journal of Spices and Aromatic Crops, 2002)
A field experiment was conducted at Hisar during winter (rabi) of 1998-99 and 1999-2000 to assess the reduction in growth and yield parameters of two susceptible fenugreek: (Trigonella foenum-graecum L.) varieties (HM 65 and T 8) due to powdery mildew disease caused by Erysiphe polygoni DC. and Leveillula taurica (Lev.) Arnaud. The disease had no significant effect on plant height and number of branches even at more than 80 per cent disease intensity. However, more than 60 per cent disease intensity significantly reduced the number of pods per plant, number of seeds per pod and test weight. Reductions of 22.8-25.6, 16.2-18.8 and 14.3-17.2 per cent pods per plant, seeds per pod and test weight, respectively were recorded in both the varieties when disease intensity was more than 80 per cent.